Pengaruh Media Sosial Terhadap Motivasi Belajar Siswa - Reski Amelia Ainun; Wahyullah Alannasir; Nursafitri Nursafitri; Shalsa Nurfitriana; Dudwinadia Dudwinadia; Aulia Faradiba (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The advancement of digital technology has rendered social media a significant aspect of students' lives, serving not only as a platform for communication and entertainment but also as a medium for learning. This research seeks to examine the effect of social media on students' motivation to learn, its function as a learning resource, and its potential to hinder educational progress. The methodology employed in this research is a Systematic Literature Review (SLR), which involves analyzing various journals and academic sources published between 2020 and 2026. The findings indicate that social media offers several benefits, including easy access to information, the availability of educational materials, enhanced learning interaction, flexibility in time management, and the promotion of independent learning among students. Conversely, social media also presents drawbacks such as diminished concentration, digital addiction, procrastination of tasks, a decrease in effective study time, and a lack of academic discipline when used excessively. Consequently, social media is not wholly beneficial or detrimental; its effects are contingent upon usage patterns, oversight, and the students' capacity to utilize it judiciously. Therefore, support from educators, parents, and educational institutions is essential to ensure that social media can serve as an effective and productive tool for learning.